2010
DOI: 10.1007/s12355-010-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane bud chips: A promising seed material

Abstract: Sugarcane is normally propagated by stalk cuttings consisting of 2 to 3 bud sett. In conventional system, about 6 -8 tons seed cane /ha is used as planting material. Establishing the sugarcane crop using bud chips in place of setts could save about 80% by weight of the stalk material, however this technology has not been scaled up at commercial levels due to poor survival of bud chips under field conditions. Present study is aimed at improving sprouting and establishment of bud chip seed stocks of sugarcane by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 1 publication
0
25
0
10
Order By: Relevance
“…The system of seedling transplantation shortens the age of plants in the field by one month compared with that of a conventional system so that late harvest can be avoided (Jain et al, 2010). The role of mycorrhiza in increasing the sugarcane yield is by increasing the number of shoots per clump, stem height and stem diameter, and improving the soil pH (pH 6.4-6.9) (Fundora et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The system of seedling transplantation shortens the age of plants in the field by one month compared with that of a conventional system so that late harvest can be avoided (Jain et al, 2010). The role of mycorrhiza in increasing the sugarcane yield is by increasing the number of shoots per clump, stem height and stem diameter, and improving the soil pH (pH 6.4-6.9) (Fundora et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In year 1977, Andhra Sugars has fabricated bud chip machine and Ramaiah et al demonstrated bud chip technology using three varieties, Co 419, Co 975 and Co 997. Further, several other workers had established that about 80% seed material can be saved by bud chip seed material [1,2]. Scientist working at NPKRR Cooperative sugar Mills reported that bud chip seedlings transplanting technique as most suitable technology for Cauvery delta areas.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Jain et al (2010), a utilização de fragmentos do colmo contendo gemas isoladas apresentam baixos índices de brotação e redução na altura inicial das plantas. Além disso, devido às limitações em relação às reservas energéticas dos fragmentos de tolete, ocorre baixa sobrevivência das gemas em condições de campo.…”
Section: Resultsunclassified
“…Além disso, essa grande massa de material para o plantio acarreta problemas de transporte e armazenamento, causando a rápida deterioração dos colmos, o que reduz a viabilidade das gemas e posteriormente a emergência (JAIN et al, 2010).…”
Section: Introductionunclassified
See 1 more Smart Citation